An intelligent control scheme for precise tip‐motion control in atomic force microscopy. Issue 2 (15th July 2015) - Wang, Yanyan; Hu, Xiaodong; Xu, Linyan
Summary: The paper proposes a new intelligent control method to precisely control the tip motion of the atomic force microscopy (AFM). The tip moves up and down at a high rate along the z direction during scanning, requiring the utilization of a rapid feedback controller. The standard proportional‐integral (PI) feedback controller is commonly used in commercial AFMs to enable topography measurements. The controller's response performance is determined by the set of the proportional (P) parameter and the integral (I) parameter. However, the two parameters cannot be automatically altered simultaneously according to the scanning speed and the surface topography during continuors scanning, leading to an inaccurate measurement. Thus a new intelligent controller combining the fuzzy controller and the PI controller is put forward in the paper. The new controller automatically selects the most appropriate PI parameters to achieve a fast response rate on basis of the tracking errors. In the experimental setup, the new controller is realized with a digital signal process (DSP) system, implemented in a conventional AFM system. Experiments are carried out by comparing the new method with the standard PI controller. The results demonstrate that the new method is more robust and effective for the precise tip motion control, corresponding to the achievement of a highly qualified image by shortening the response time of the controller. SCANNING 38:93–99, 2016. © 2015 Wiley Periodicals, Inc.